Misoprostol Versus Oxytocin for Induction of Labour at Term and Post Term Pregnancy of Primigravida - Tripathi, Malati; Adhikari, Ayushma; Neupane, Bibhushan (Journal of Universal College of Medical Sciences, 2018)
Introduction: To compare effectiveness and safety of sublingually administered misoprostol and intravenously infused 10 units of oxytocin for labor induction at term and post term pregnant women in Gandaki Medical College Teaching Hospital (GMCTH). Materials and methods: This is a prospective study conducted in Department of Obstetrics and Gynaecology in Gandaki Medical College and performed on 120 patients of primigravida with cephalic presentation at term and post-term pregnancy. Patients were given 50µg sublingual misoprostol 6 hourly (two doses) and 5 units of oxytocin in 500ml RL started from 10 drops up to 60 drops till effective contraction occur with maximum of 10 units oxytocin. Maternal and fetal outcomes were observed. Collected data were analyzed using SPSS and MS Excel. Results: There were no significant differences between the groups concerning time duration between inductions to delivery time, indications of caesarean section, different modes of delivery and for the Apgar score at one and five minutes. Conclusion: Both oxytocin and misoprostol are effective and safe for induction of labour.